Madrasah dan Jenjang Karir di Negara Usmani pada Masa Klasik (1300-1600) - Frial Ramadhan Supratman (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2020)
This article focuses on history of education in Muslim world in from fourteenth until seventeenth centiuries in Ottoman state. As the most important Muslim state in the world during classical period (1300-1600), Ottoman state became the role model of education system for Muslims. Influenced by Seljuk Anatolia state, Ottoman built education through medrese system controlled by state. The system supported the state to design career development for its subject. In addition to devÅŸirme system, medrese system provided large opportunity for its subject to obtain career as teacher and professor (mÃ¼derris), judge (kadÄ±), and bureaucrat (kalemiye). Research method in this article are qualitative and bibliographical research. Author examines historical reseources to analyze research problem. The aim of research is to observe and analyze relationship between education system and career development in Ottoman state. According to this research, author concludes that medrese system in Ottoman state provided opportunity for its subject to participate in social mobility thorugh its career in government circle.